Flocking control for two-dimensional multiple agents with limited communication ranges. Issue 9 (2nd September 2021) - Binh, Nguyen Thanh; Dai, Pham Duc; Quang, Nguyen Hong; Ty, Nguyen Trung; Hung, Nguyen Manh
Abstract : In all existed researches on flocking control for multi-agent systems, each agent is modelled as a single point or covered by an circle, ellipse or rectangle; however, in case of limited space traffic systems, many complex vehicles cannot be fitted in these agent shapes. This paper proposes a distributed control law for two-dimensional multiple agents considered as arbitrarily polygonal shapes under limited communication ranges. The proposed control laws guarantee all flocking properties: each agent stays close to its nearby neighbours, no collision occurs in group of agents and velocity of each agent converges to a common vector. The designed control law based on a new anti-collision condition and potential function approach aims at dealing with the issue of collisions between agents. Further, the control signals are bounded and differentiable despite of agent's limited communication ranges and non-smooth boundary in agent shapes. Numerical simulations are implemented to demonstrate the performance of proposed control law for multiple agents with the same and different shapes.